Early life overfeeding impairs spatial memory performance by reducing microglial sensitivity to learning. Issue 1 (December 2016) - De Luca, Simone; Ziko, Ilvana; Sominsky, Luba; Nguyen, Jason; Dinan, Tara; Miller, Alyson; Jenkins, Trisha; Spencer, Sarah
Abstract Background Obesity can lead to cognitive dysfunction including poor performance in memory tasks. However, poor memory is not seen in all obese humans and takes several months to develop in animal models, indicating the adult brain is relatively resistant to obesity's cognitive effects. We have seen that, in the rat, overfeeding for as little as 3 weeks in early life leads to lasting obesity and microglial priming in the hypothalamus. Here we hypothesized that microglial hyper-sensitivity in the neonatally overfed rats extends beyond the hypothalamus into memory-associated brain regions, resulting in cognitive deficits. Methods We tested this idea by manipulating Wistar rat litter sizes to suckle pups in litters of 4 (overfed) or 12 (control). Results Neonatally overfed rats had microgliosis in the hippocampus after only 14 days overfeeding, and this persisted into adulthood. These changes were coupled with poor performance in radial arm maze and novel object recognition tests relative to controls. In controls, the experience of the radial arm maze reduced cell proliferation in the dentate gyrus and neuron numbers in the CA3. The learning task also suppressed microglial number and density in hippocampus and retrosplenial cortex. Neonatally overfed brains had impaired sensitivity to learning, with no neuronal or cell proliferative effects and less effective microglial suppression. Conclusions Thus, early life overfeeding contributes to a long-term impairment in learning and memory with a likely role for microglia. These data may partially explain why some obese individuals display cognitive dysfunction and some do not, i.e. the early life dietary environment is likely to have a vital long-term contribution.